ROOT STRENGTH MEASUREMENTS OF VETIVER AND RUZI GRASSES - Chairat Teerawattanasuk; Jindarat Maneecharoen; Dennes T. Bergado; Panich Voottipruex; Le Gia Lam (International Association of Lowland Technology, 2014)
This paper aims to study effect of roots of vegetation on the stability of soil along slopes and also soil erosion. The effects of root reinforcement depend on the morphological characteristics of the root system, the tensile strength of grass roots, and the spatial distribution of the roots in the soil. The experiments were carried out to evaluate the root tensile strength of two different grasses namely: Vetiver and Ruzi grasses, by conducting the laboratory tensile tests and field direct shear tests. For each type of grass, single root specimens were sampled and tested for their ultimate tensile strength and Young’s modulus in the laboratory tests. The results of laboratory tests revealed the significant correlations between root diameter and tensile force or tensile strength and Young’s modulus of Ruzi and Vetiver grasses. In addition, large scale field direct shear tests were carried out involving roots of Vetiver and Ruzi grasses to evaluate the contributions of their root systems to the soil shear strength. Vetiver roots contributed higher components of shear strength compared to Ruzi grass. However, it was found that the combination of Ruzi and Vetiver grass roots yielded much better effects than Vetiver grass alone. It can be concluded that the Vetiver grass roots help enhanced the shear strength for soil reinforcement while the short roots of Ruzi grass can help control surface soil erosion.